Sticking to her guns - Daniels, B. J. (Daniels, B. J. Colt Brothers investigation, 2022)
"Tommy Colt is stunned when his childhood best friend--and love--Bella Worthington abruptly announces she's engaged to their old-time nemesis! Knowing her better than anyone, Tommy's convinced she'd only agree to a sham marriage if something was dangerously wrong. Now Colt Brothers Investigations' newest partner is racing to uncover the truth and ask Bella a certain question ... if they survive."--Page 4 of cover.